Nasolabial shape and aesthetics in unilateral cleft lip and palate: an analysis of nasolabial shape using a mean 3D facial template. Issue 2 (February 2021) - Kuijpers, M.A.R.; Maal, T.J.J.; Meulstee, J.W.; Carels, C.E.L.; Bronkhorst, E.M.; Bergé, S.J.; Fudalej, P.S.
Abstract: The aim of this study was to determine the amount of deviation in nasolabial shape in patients with a cleft compared with an average non-cleft face, and to assess whether this difference is related to nasolabial aesthetics. Three-dimensional stereophotogrammetric images of 60 patients with a unilateral cleft were used. To quantify shape differences, four average non-cleft faces were constructed from stereophotogrammetric images of 141 girls and 60 boys. Three-dimensional shape differences were calculated between superimposed cleft faces and the average non-cleft face for the same sex and age group. Nasolabial aesthetics were rated with the modified Asher-McDade Aesthetic Index using a visual analogue scale (VAS). Mean VAS scores ranged from 51.44 to 60.21 for clefts, with lower aesthetic ratings associated with increasing cleft severity. Shape differences were found between cleft faces and the average non-cleft face. No relationship was found for the VAS, age, and sex, except that a lower VAS was related to a higher nose and lip distance between the superimposed cleft and average non-cleft faces for nasal profile ( P = 0.02), but the explained variance was low ( R 2 = 0.066). In conclusion, except for nasal profile, nasolabial aesthetics were not influenced by the extent of shape differences from the average non-cleft face.